Analysis of Mathematical Creative Thinking Ability Based on Students' Academic Ability - Madya, Nana Karina; Angraini, Lilis Marina; Bonyah, Ebenezer (EDUPEDIA Publisher, 2025)
This study aims to analyze students' mathematical creative thinking skills based on their academic abilities. The essential elements that include creative thinking are 1) fluency; 2) flexibility; 3) originality; 4) Elaboration. This study uses descriptive research with a qualitative approach. The subject in this study is a student of Junior High School 4 Koto Gasib. The subject of this study is grade IX students as many as 28 purposive sampling students who have studied the data collection techniques used in this study, namely in the form of mathematical creative thinking ability test questions on TVLES material and interviews. The results of the analysis showed that the average score was 56.25 based on the four indicators, students had quite high creative thinking skills. The average ability of students to think creatively in the Elaboration category is 89% which indicates a very high Average ability of students to think creatively in the originality category is 75%, the average ability of students to think creatively in the flexibility category is 23%, the average ability of students to think creatively in the fluency category is 38%.